Inevitability of Environmental CSR in Dire Environmental Difficulties and its Ways-Out: Bangladesh Perspective - Rashed, Al Karim (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://ijbt.unimap.edu.my